Examining the effectiveness of Prostatic hyperplasia education on the level of participant’s knowledge and awareness - Hari Krismanuel; Purnamawati Tjhin (PLoS ONE, 2025)
Prostatic Hyperplasia (PH) is a common condition among older men, contributing significantly to Lower Urinary Tract Symptoms (LUTS). Despite available medical treatments, there is a lack of public awareness about PH, resulting in late diagnoses. This study offers a novel approach by using a community-based educational intervention to increase knowledge of PH, leveraging the International Prostatic Symptom Score (I-PSS) as a tool for educating elderly men in Bogor, Indonesia. This study aims to evaluate the effectiveness of community-based education on prostatic hyperplasia (PH) in enhancing knowledge and awareness among elderly male participants, addressing the gap in public awareness and the need for early detection, unlike prior studies conducted in clinical settings. By utilizing the International Prostatic Symptom Score (I-PSS), this study provides a structured approach to community health education and symptom self-assessment. A mixed-methods, quasi-experimental pretest-posttest design involved 32 participants aged ≥ 60 years in Bogor, Indonesia. Quantitative data assessed changes in knowledge before and after the intervention, while qualitative insights were gathered through post-education discussions. Statistical analyses, including paired t-tests and effect size (Cohen’s d), were conducted to measure the intervention’s impact. This study is unique in its application of I-PSS for community education and its combination of quantitative and qualitative data to measure knowledge improvement and explore participant perceptions. Significant knowledge improvement was found post-intervention (mean increase: 8.9, p < 0.001, Cohen’s d = 0.82). The integration of qualitative feedback highlighted the relevance and clarity of the intervention while also identifying remaining knowledge gaps, revealing its holistic impact on the participants. The novelty of this study lies in its community-based approach using I-PSS, which is an underexplored method in educating about PH. The results provide strong evidence for using structured community education to promote early detection and improve PH awareness. Future studies could benefit from including control groups and testing this approach in other regions for broader applicability. This study demonstrates the effectiveness of a community-based educational intervention using the International Prostatic Symptom Score (I-PSS) in improving knowledge and awareness about Prostatic Hyperplasia (PH) among elderly men. The findings suggest that integrating tools like the I-PSS in community health programs can empower individuals to self-assess their symptoms, promote early detection, and reduce the burden of delayed diagnoses. These results underscore the potential of scalable, low-cost interventions to address health education gaps in similar low-resource settings globally.